Some evidence on Gerstmann's syndrome: A case study on a variant of the clinical disorder. - Basagni, Benedetta; Luzzatti, Claudio; De Tanti, Antonio; Bozzetti, Francesca; Crisi, Girolamo; Pinardi, Chiara; Errante, Antonino; Fogassi, Leonardo (Brain & Cognition, 2021)
We describe the case of a bilingual patient with persistent symptoms largely, although not fully, consistent with those that are usually reported in Gerstmann's syndrome. Twenty months after a spontaneous primary intracranial hemorrhage, the patient was evaluated with a series of neuropsychological tasks and underwent an MRI investigation based on Diffusion Tensor Imaging probabilistic tractography. The patient suffered from dysgraphia (difficulty in the access to the graphemic representation of letter forms), autotopoagnosia (difficulties in locating body parts on verbal command), right-left confusion (difficulties in localizing right and left side of symmetrical body parts), and number processing/calculation impairments (predominant difficulties on transcoding tasks). Probabilistic tractography revealed a relatively spared superior longitudinal fasciculus and severe damage to the subcortical white matter connecting the angular gyrus with other parietal regions, such as the intraparietal sulcus and the supramarginal gyrus. Within the framework of the contemporary cognitive accounts of Gerstmann's syndrome, the case supports the assumption of an anatomical intraparietal disconnection more than a functional Grundstörung (core impairment).